A STUDY ON THE ABILITY OF THE SIXTH-SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM AT FKIP UNIVERSITAS RIAU IN ANALYZING SHORT STORIES - Zuarni, Witri; Azahar, Fadly; Erni, Erni (TELL - US JOURNAL, 2025)
This study aimed to investigate the ability of sixth-semester students of the English Study Program at FKIP Universitas Riau in analyzing the intrinsic elements of short stories. This research employed a descriptive quantitative method. The sample consisted of 37 students from one class (6A) , selected through cluster random sampling. The instrument used was a semi-essay test where students were asked to analyze the elements of one chosen short story from three options. The analysis focused on five intrinsic elements: setting, character, point of view, plot, and theme. The findings revealed that the students' overall ability was in the "average to good" category, with a total average score of 77.2. Students performed best in analyzing Point of View (average score 78.7) and Character (78.0). Conversely, students faced the most difficulty with the more abstract elements of Theme (76.1) and Plot (77.3). The study concludes that while students possess a solid ability to analyze concrete literary elements, there is a need for improvement in analyzing abstract components like plot and theme.